2020
DOI: 10.9770/jesi.2020.7.4(26)
|View full text |Cite
|
Sign up to set email alerts
|

Relevance and social responsibility of sustainable university organizations: analysis from the perspective of endogenous capacities

Abstract: The university social relevance is the effective management of the academic functions in a committed way, from which it analyzes, studies, and investigates the problems, needs, requirements of the social environment to identify, characterize, rank them. And a model social action to the research, teaching, extension, and training of professionals, consistent with social needs, linked to the realities of the various contexts of human performance that neo university organizations, rescuing sustainability with hum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 8 publications
1
10
0
1
Order By: Relevance
“…This study presents a methodological proposal as a product of the experience and analysis of comparatives of different qualitative-naturalistic routes in the management sciences [23,24], which allowed detecting methodological gaps characterized by lack of scientific rigour from the construction of the guiding categories to the presentation of the results. To this end, a detailed methodological proposal is presented in Fig.…”
Section: Qualitative-naturalistic Research Routementioning
confidence: 99%
“…This study presents a methodological proposal as a product of the experience and analysis of comparatives of different qualitative-naturalistic routes in the management sciences [23,24], which allowed detecting methodological gaps characterized by lack of scientific rigour from the construction of the guiding categories to the presentation of the results. To this end, a detailed methodological proposal is presented in Fig.…”
Section: Qualitative-naturalistic Research Routementioning
confidence: 99%
“…Esta es una estrategia para la acción, es decir, "la capacidad de las comunidades locales de liderar su propio proceso de desarrollo, unido a la movilidad de su potencial de desarrollo, es lo que permite dar a esta forma de desarrollo el calificativo de desarrollo endógeno" (Vázquez, 1999, p. 30). Esto sugiere a las comunidades locales, hacer lo posible por desarrollar sus potencialidades para generar tanto oportunidades de trabajo, como desarrollo económico y social a sus habitantes (Hernández, Ravina & Chumaceiro, 2020).…”
Section: Bases Sobre Las Que Se Fundamenta El Microcréditounclassified
“…In this sense, students and teachers provide a virtual meeting through spaces that aim to improve the development of communication skills, technology and training, allowing the student's accessibility from anywhere, generating discussions of issues beyond the class schedule. However, the scientific literature Hernández García de Velazco, et al [4], Vargas Herrera and Moya Marchant [5] have demonstrated the existence of resistance to change in the handling of interactive platforms, which awakens interest in the study of the use of interactive platforms and the process of knowledge management. Studying the use of interactive platforms, allows the academic community to determine the failures in the process of change in the modalities of studies, which must meet educational quality criteria.…”
Section: Introductionmentioning
confidence: 99%